Pengaruh Fraksi Volume Polyurethane terhadap Uji Tarik dan Lentur Komposit Pegas Daun (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
Leaf springs serve as vehicle weight supports and vibration dampers from uneven roads. Reducing vehicle weight can support fuel consumption reduction. The use of composite materials allows for a reduction in leaf spring weight without reducing load capacity and stiffness. The purpose of this study was to find the composition of composite leaf springs with a polyurethane matrix that were resistant to tensile and flexural tests using e-glass, epoxy, and polyurethane materials. This study used an experimental method, in which specimens were tested using a tensile and flexural testing machine. The variations included polyurethane matrices of 10%, 20%, and 30%. The data was statistically analyzed using Excel to determine the significant effect of the variables. The results showed the effect of polyurethane variation on the composite. The tensile test showed that the greatest tensile stress was on the 30% polyurethane specimen at 1.574 N/mm² and the smallest was on the 10% specimen at 7.007 N/mm². In the flexural test, the greatest effect on flexural strength was observed in the 30% specimen at 14.36 MPa and the smallest in the 10% specimen at 25.82 MPa. Without the addition of polyurethane, the tensile stress was 39.678 N/mm² and the flexural strength was 157.09 MPa. Conclusion: The addition of polyurethane reduces the mechanical strength of composite leaf spring material without polyurethane addition.